(untitled) (Research, Society and Development, 2020)
Objective: to analyze the strategies proposed in the scientific literature for the promotion of active aging in the Brazilian scenario, and to identify the possible gaps that prevent it from becoming a reality. Method: integrative review carried out in the Scientific Electronic Library (Scielo), Latin American and Caribbean Literature in Health Sciences (Lilacs), and Pubmed databases, in September 2020, with the descriptors; healthy aging, ageing well, aging healthy, aging successfully and good aging, in the Portuguese, Spanish and English languages, published between 2016 and 2020 that addressed at least one of the dimensions of the factors determined by the World Health Organization (WHO) for the development of active aging. Results: Seventeen studies were integrated into the research because they addressed the dimensions defined by the WHO for the development of active aging, and a single dimension was addressed in most of them: the social dimension is widely addressed in 11, cultural and leisure dimension in 1; the other 4 address two dimensions together, and none address the economic dimension. Conclusion: The scientific literature has demonstrated ways to promote active aging, however, many dimensions are still little explored.